2010
DOI: 10.1007/s00455-010-9288-y
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Preventive Rehabilitation Trial in Advanced Head and Neck Cancer Patients Treated with Chemoradiotherapy: Feasibility, Compliance, and Short-term Effects

Abstract: The aim of this study was to assess the effect of (preventive) rehabilitation on swallowing and mouth opening after concomitant chemoradiotherapy (CCRT). Forty-nine patients with advanced oral cavity, oropharynx, hypopharynx and larynx, or nasopharynx cancer treated with CCRT were randomized into a standard (S) or an experimental (E) preventive rehabilitation arm. Structured multidimensional assessment (i.e., videofluoroscopy, mouth-opening measurement, structured questionnaires) was performed before and 10 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
190
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(196 citation statements)
references
References 42 publications
2
190
1
3
Order By: Relevance
“…Reduced systemic health, financial difficulties and family problems could be some of the main reasons for this inadequate compliance to the study. Other authors reported inadequate compliance of a large number of patients because of death before the completion of study, refusal for a re-examination, withdrawal from the study, poor systemic health, administrative and technical difficulties [29]. Increased compliance might be achieved with the contribution of the appropriately educated dentist and the support and maintenance of oral health in head and neck cancer patients, as it was shown in the literature [33].…”
Section: Eortc Qlq Head/neck35mentioning
confidence: 95%
“…Reduced systemic health, financial difficulties and family problems could be some of the main reasons for this inadequate compliance to the study. Other authors reported inadequate compliance of a large number of patients because of death before the completion of study, refusal for a re-examination, withdrawal from the study, poor systemic health, administrative and technical difficulties [29]. Increased compliance might be achieved with the contribution of the appropriately educated dentist and the support and maintenance of oral health in head and neck cancer patients, as it was shown in the literature [33].…”
Section: Eortc Qlq Head/neck35mentioning
confidence: 95%
“…Historically, treatment approaches have been reactive, with rehabilitation administered after medical intervention (either surgical or non-surgical). However, emerging evidence [15][16][17][18][19] has instigated a shift towards the use of preventative dysphagia rehabilitation, based on the premise that proactively exercising swallowing structures known to be negatively impacted by radiation may limit the extent of (C)RT-induced dysfunction [20].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the findings of three RCTs [16,17,19] have demonstrated that patients who underwent prophylactic swallowing rehabilitation protocols pre-and/or during (C)RT had superior outcomes across a range of swallowing indexes following treatment, including: improved functional swallowing outcomes; significantly less deterioration in head and neck muscle composition; less decline in mouth opening, taste and smell; better preservation of salivary PHYSIOLOGICAL SWALLOWING DEFICITS FOLLOWING (C)RT FOR HNC 4 flow; and fewer patients requiring or dependent on gastrostomy tube feeding. However, despite each reporting some degree of positive findings for prophylactic swallowing exercises in the (C)RT-HNC population, examination of the study protocols reveals wide variability in the exercises employed, with each study reporting use of different groups of therapy tasks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research based on pilot studies and small scale trials suggests that the potential benefit from interventions to promote general physical activity and exercise before, during and after treatment may be of value for this patient group [11][12][13], and that HNC patients may also benefit from exercises before and during treatment to promote strength, mobility, and endurance of base of tongue, pharyngeal constrictors, and suprahyoid strap muscles [14][15][16][17].…”
mentioning
confidence: 99%